Morphostatistical analysis of Maastrichtian populations of Guembelitria from El Kef, Tunisia - Arz, José A.; Arenillas, Ignacio; Nañez, Carolina Adela (The Journal of Foraminiferal Research)
Three species of Guembelitria with regular triserial arrangement are recognized in the late Maastrichtian, based on biometric measures of specimens from El Kef (Tunisia) and morphostatistical analysis. They are mainly recognized based on their test height and rate of increase in size of the chambers. Guembelitria blowi, nov. sp. is proposed for the short-spired morphotypes that were previously ascribed to Guembelitria trifolia. Guembelitria cretacea Cushman, 1933, is restricted to medium-spired morphotypes, and Guembelitria dammula Voloshina, 1961, to high-spired morphotypes. The three morphospecies have a papillate test surface, usually with pore-mounds, but some specimens exhibit imperforate papillae. The origin of this variability in the guembelitrid test surface might be linked to ecophenotypy or ontogeny, but the presence of cryptic species cannot be ruled out. Fil: Arz, José A. Universidad de Zaragoza; España Fil: Arenillas, Ignacio. Universidad de Zaragoza; España Fil: Nañez, Carolina Adela. Secretaria de Industria y Mineria. Servicio Geológico Minero Argentino. Subsecretaria de Mineria; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina